FACTORS AFFECTING BLIND STUDENTS’ ENGAGEMENT IN LEARNING ENGLISH - Galuh Nurul Indah Asri; Firdaus Adrianto Adrianto (Fakultas Ilmu Budaya, Universitas Brawijaya, 2021)
Universitas Brawijaya (UB) with the assistance of Pusat Studi dan Layanan Disabilitas (PSLD) have implemented an inclusive education environment, as the need for equal education chance for different abilities Indonesians. There is an assumption that engagement from a combination of language learning or learning language’s cognitive, social, and affective aspects can affect the learning process and academic achievement of a special need student. To reach the research objective, interview sessions and classroom observations session were aimed at measuring the students' language learning engagement based on three-domains; cognitive, affective and social, in students’ perspective and ongoing activities. This research shows fluctuate results based on the interviews and observations data of two blind students. The main engaged factors found are positive teaching approaches and attitudes, also both students’ learning autonomy.